Periodontal Pathogens Promote Oral Squamous Cell Carcinoma by Regulating ATR and NLRP3 Inflammasome - Yao, Yufei; Shen, Xin; Zhou, Maolin; Tang, Boyu (Frontiers in Oncology, 2021)
Periodontitis is closely related to oral cancer, but the molecular mechanism of periodontal pathogens involved in the occurrence and development of oral cancer is still inconclusive. Here, we demonstrate that, in vitro, the cell proliferation ability and S phase cells of the periodontitis group (colonized by Porphyromonas gingivalis and Fusobacterium nucleatum, P+) significantly increased, but the G1 cells were obviously reduced. The animal models with an in situ oral squamous cell carcinoma (OSCC) and periodontitis-associated bacteria treatment were constructed, and micro-CT showed that the alveolar bone resorption of mice in the P+ group (75.3 ± 4.0 μm) increased by about 53% compared with that in the control group (48.8 ± 1.3 μm). The tumor mass and tumor growth rate in the P+ group were all higher than those in the blank control group. Hematoxylin–eosin (H&E) staining of isolated tumor tissues showed that large-scale flaky necrosis was found in the tumor tissue of the P+ group, with lots of damaged vascular profile and cell debris. Immunohistochemistry (IHC) of isolated tumor tissues showed that the expression of Ki67 and the positive rate of cyclin D1 were significantly higher in tumor tissues of the P+ group. The qRT-PCR results of the expression of inflammatory cytokines in oral cancer showed that periodontitis-associated bacteria significantly upregulated interleukin (IL)-6, tumor necrosis factor (TNF)-α, IL-18, apoptosis-associated speck-like protein containing a CARD (ASC) (up to six times), and caspase-1 (up to four times), but it downregulated nuclear factor (NF)-κB, NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3), and IL-1β (less than 0.5 times). In addition, the volume of spleen tissue and the number of CD4+ T cells, CD8+ T cells, and CD206+ macrophages in the P+ group increased significantly. IHC and Western blotting in tumor tissues showed that expression levels of γ-H2AX, p-ATR, RPA32, CHK1, and RAD51 were upregulated, and the phosphorylation level of CHK1 (p-chk1) was downregulated. Together, we identify that the periodontitis-related bacteria could promote tumor growth and proliferation, initiate the overexpressed NLRP3, and activate upstream signal molecules of ATR-CHK1. It is expected to develop a new molecular mechanism between periodontitis-related bacteria and OSCC.